Secure and efficient protocol for fast handover in 5G mobile Xhaul networks. (15th January 2018) - Sharma, Vishal; You, Ilsun; Leu, Fang-Yie; Atiquzzaman, Mohammed
Abstract: Mobile networks are observing an all time increase in the number of users and services. These networks have hit the 5G requisites in no time. Current service providers are aiming at resolving issues of subsisting networks by exploiting the capacity and coverage enhancement features of 5G. With a broad spectrum, it has now become more facile to accommodate an astronomically immense number of devices each having multiple applications authoritatively mandating network accessibility. Despite these advantages, such networks suffer from several issues cognate to smooth operations of fronthaul and backhaul, such as interference management, link-reliability, flatness, security and flexibility. Integrating fronthaul and backhaul together as a Xhaul is suggested as one of the efficient solutions for handling these issues. Xhaul forms integrated planes which use heterogeneous switches for high optical transmissions. Despite being efficient, Xhaul links are weak in terms of security. The situations will be more serious, particularly when a massive number of User Equipment (UE) and IoT devices are now connected to it. This issue is further raised when the terminal fortifying the fronthaul and backhaul moves leading to the formation of mobile Xhaul network. The current security solutions for WiFi, WiMax, WiBro, 4G/LTE are unable to fortify privacy and perfect forward secrecy in mobile Xhaul network, which is a quandary targeted in this paper. To resolve these issues, a novel key exchange and authentication protocol is proposed, which is capable of securing Xhaul links for a moving terminal in the network. The proposed approach is tested utilizing mobile ground node and drone as moving terminal across multiple hubs. The formal analysis utilizing BAN logic and AVISPA tool slake the security requisites and performance evaluation justifies the efficiency in comparison with the existing solutions.